Fabrication and characterization of barium strontium titanate film based biosensor - Tan, Lay Im (2009)
In this project, biosensors based on a sol-gel derived Barium Strontium Titanate (BST) composite film are studied. Poly(TMS-r-NHS) [TMS: 3-(trimethoxysilyl)propyl methacrylate; NHS: N-hydroxysuccinimide] is used to modify the BST surface for protein immobilization. Two types of biosensors were developed and investigated. First, Bovine Serum Albumin (BSA) was immobilized on the poly(TMS-r-NHS) followed by anti-BSA. On the second type of biosensors, cloned Epstein-Barr virus (EBV) was imlTIobilized on the poly(TMS-r-NHS) followed by anti-EBV. Significant impedance increlnents were observed on both biosensors. These impedance increments were attributed to three factors.